RURAL DEVELOPMENT WITH THE EMPHASIS ON THE SIGNIFICANT ROLE OF BUFFALO RAISING IN DEVELOPING COUNTRIES - Naderfard, Hamidreza (Proceeding Buffalo International Conference, 2013)
In the spite of quick trend the technical and scientific progress and increasing improvement of mankindâs life in all over the world, still a huge human population are suffering from different socio-economic and cultural deficiencies suchÂ as:Â a) Illiteracy,Â b) Malnutrition,Â c) LackÂ or in-sufficient medical and health care mortality in rural areas of developing countries. Indices show that along with modernization and extension of big cities, cultural and socio-economic problems are being increased,Â parallel. In such a condition, development of rural areas is an inevitable necessity, because stillÂ aboutÂ 50% of human population live in rural areas and are deprived ofÂ primary possibilities, otherwise, they migrate to big cities and createÂ socialÂ problems, In order to approach rural development, agriculture is the most important because theÂ vast majority of rural poor depend on agriculture for their livelihoods. Therefore, all policy makers must unite the national and international agencies and address them toward agriculture development in rural areas. In this connection, animal husbandry sector plays a vital role in providing nutritional security (Meat and milk) and occupation. Surely, Buffaloes contribute significantly to the sustainability of mixed crop-livestock farming systems as well as to farmerâs income and production of milk, meat and draft power in the most Asian countries, during centuries. Because of miraculous digestive system, buffaloes are able to convert by-products and the wastages of agriculture and food industries to high nutritive milk and meat. But, in the spite such a unique potential, because of poverty of buffalo raisers, the buffaloes are not able to show their best performance. So, the basic and important duty of governments, policy makers, NGOâs, scientists and experts is the comprehensive support of buffaloes and conserve this unique genetic resource for future generation in world.